The rescission action as disruptive cause of prescription (Research, Society and Development, 2022)
In the Constitutional State, law and society coexist, basically, due to the expectation of social harmony that the former (the law) is able to provide to the second (society), according to the social values in vogue and positive legal norms, equally responsible for ensuring legal certainty. One of the institutes capable of providing security in the face of social conflicts is the definitive character of the legal-procedural figure of the thing judged, with a view to verifying, at any given moment, the immutability or non disputability of the decision-making content of the judgment, although the respective effects, in principle, are modifiable by the will of the parties, always, with the exception of the legal hypotheses of unavailable right. Moreover, although it has the purpose of disconstituting the decision of merit, the rescission action is also influenced by the time factor due to the same need for legal certainty applicable to procedural relations, specially facing the statute of limitations. Thus, based on a review of specialized procedural bibliography, this paper analyzed the jurisprudential reasons for which the rescission action is addressed as a cause of interruption of the prescription, the effects of which go back to the date of the original lawsuit.